A CFD Study Of A Partial Combustion Lance - Law, Woon Phui; Jolius, Gimbun (Taylor's University, 2015)
This paper presents a computational fluid dynamics (CFD) simulation of a partial combustion lance (PCL) aiming to evaluate the effect of oxygen flowrate on its performance. At first, the modelling strategy was developed by evaluating the effect of discretization, pressure interpolation scheme and turbulence models on the prediction accuracy. Three turbulence models namely standard kε (SKE), realizable k-ε (RKE) and renormalized (RNG) k-ε were used. Combustion was modelled using the species transport model, whereas the heat transfer was calculated by considering a combined convection-radiation boundary condition. The best CFD prediction was obtained using the thirdorder MUSCL, PRESTO pressure interpolation scheme and SKE, yielding an error of 4.79% from the experimentally measured temperature. It was found that 40% increase in oxygen flowrate increased the peak combustion temperature of the PCL by about 12%. Dual lance was found to be more effective than the single lance operating at a similar flowrate. The finding obtained from this work may be useful for design retrofits of a PCL.